Konsep Administrasi Pendidikan - Meti Fatimah; Ahmad Yasir Al Amin; Mahmud Darul Kurniyadi (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
In this era of widespread globalization, the role of administration has become increasingly important in several different ways. The importance of an educational administration system to be implemented has become one of the benchmarks of educational quality, especially in the teaching and learning process, although its implementation has not been maximized. With proper management, educational goals can be achieved effectively and efficiently. Educational administration is a crucial aspect of managing an effective and efficient educational system. This study aims to analyze the role and importance of educational administration in improving the quality of learning. The method used is a qualitative approach with documentation techniques, involving the collection of data from various official documents and reports related to the practices of educational administration. The research findings show that educational administration significantly contributes to curriculum planning, resource management, as well as the evaluation and supervision of the teaching and learning process. These findings are expected to provide insights for policymakers and education practitioners to continue improving the quality of education in Indonesia. Therefore, it is important for all parties involved, including the government, institutional managers, educators, and the community, to collaborate in supporting the educational administration process. Investing in the improvement of educational administration quality is a vital step to ensure the development of high-quality human resources in the future.